REMAJA KERING DALAM PEMBACAAN DURUM [Lonely Teenagers in “Durum” Reading] - Resti Nurfaidah (TOTOBUANG, 2018)
This article entitled "The exhaustic Adolescent on Durum Reading". Durum is one of the compulsary scripts in Festival Drama Sunda Basa 2017. Durum is a massive script - solid in  characters  and content of the story-. The script conveys factors that cause conflict in teenagers life and the impact that occurs due the losing thefamily’s ideality  . The identification problem in this artical was just focused on adolencent’s conflict and family along its impact against himself/herself and their surroundings. The purpose of this study  revealed the background of their conflict through the symbolof each sceneand their psychological aspects This artical used semiotics of John Fiske and developmental psychology of Hurlock as its theoretical concepts.  Anyway, the research method used qualitative with descriptive analysis. The results showed that there were intergenerational gap among adolescents with all their contemporary values with the older generation and social values that wer considered as an old-fashioned; lossing of closeness and harmonious communication between parent and adolescent, as well as between parents themselves; the high pressure of hedonistic and materialistic life; also an individualist lifestyle that no longer understood the meaning of understanding and caring among people. The exhaustic adolescent represented family and environtmental disharmony.Artikel ini berjudul “Remaja Kering dalam Pembacaan Durum”. Durum merupakan salah satu naskah unggulan dalam Festival Drama Basa Sunda 2017. Durum merupakan naskah yang masif (padat dalam pemeranan dan muatan cerita). Naskah tersebut menyampaikan faktor-faktor penyebab timbulnya konflik dalam kehidupan remaja dan dampak yang terjadi akibat kehilangan idealitas di dalam lingkungan keluarga. Identifikasi masalah dalam artikel ini dibatasi pada konflik remaja dan lingkungan keluarganya serta dampaknya terhadap diri si remaja maupun lingkungan di sekitarnya. Tujuan penelitian ini adalah untuk mengungkapkan latar terjadinya konflik remaja melalui telaah pada simbol adegan serta aspek psikologis remaja. Konsep teoretis yang digunakan dalam artikel ini adalah semiotika John Fiske dan psikologi perkembangan Hurlock. Metode penelitian yang digunakan ialah kualitatif dengan analisis deskriptif. Hasil yang diperoleh dalam penelitian tersebut adalah adanya kesenjangan antargenerasi: antara remaja dengan segala nilai kontemporernya dengan generasi tua dan nilai-nilai sosial yang dianggap kolot; hilangnya kedekatan dan komunikasi harmonis antara orangtua dan remaja, serta antarorang tua sendiri; tekanan kehidupan hedonistis dan materialistis yang cukup tinggi; pola hidup individualis yang tidak lagi memahami arti pengertian dan kepedulian antarsesama manusia. Remaja kering merupakan bukti atas ketidakharmonisan keluarga dan lingkungan setempat.